한반도 정전체제와 북핵체제를 넘어: 불완전 주권성의 전개와 극복 - 전재성; Chaesung Chun (한국과 국제정치, 2023)
이 글은 한국전쟁 이후 정전체제가 어떻게 변화되어 왔는지 시기구분을 하고, 각 시기별 남북관계의 변화 과정을 남북한 주권적 지위의 변화, 남북한 군사력 균형, 국제정치구조 등 측면에서 분석한다. 냉전이 종식되면서 북핵체제가 발생하는데 북핵문제의 발생 과정, 이후의 북핵문제의 변화 및 한반도 정전체제의 변화도 중요한 연구 주제이다. 북핵체제가 정전체제를 완전히 대체하는 성격을 가진 포괄적 체제라고 보기는 어렵지만, 변화된 미단극 패권체제라는 국제정세와 남북 간의 군사적 불균형, 한국 주도의 한반도 정세 속에서 북한이 핵개발을 통해 정전체제를 무력화하여 군사력을 증진시키고 생존을 모색했다는 점에서 차별화된다. 2022년 미중 전략경쟁이 심해지는 가운데 우크라이나 전쟁이 발발하고 소위 탈냉전의 종식을 논하는 현 시점에서 북핵문제가 어떠한 국면을 맞이하고 있고 향후 한반도 안보구조가 어떻게 변화되는지, 미래 한반도 거버넌스와 통일의 미래를 둘러싼 어떠한 대안이 논의되고 있는지도 살펴본다. This article explores how the armistice system has changed since the Korean War, and analyzes the process of change in inter-Korean relations in each period regarding changes in the sovereign status of the two Koreas, the balance of military power between the two Koreas, and the international political structure. As the Cold War ended, the North Korean nuclear regime emerged. The process of the North Korean nuclear issue, subsequent changes in the North Korean nuclear issue, and changes in the armistice system on the Korean Peninsula are also important research topics. Although it is difficult to see the North Korean nuclear regime as a comprehensive system that completely replaces the armistice regime, North Korea neutralizes the armistice regime through nuclear development in the face of the post-Cold War US unipolarity, the military imbalance between the two Koreas, and the situation on the Korean Peninsula led by South Korea. It is differentiated in that it promoted military power and sought survival. In 2022, amid intensifying strategic competition between the U.S. and China, the war in Ukraine broke out with the discussion of the end of the so-called post-Cold War. This article also examines how the North Korean nuclear issue evolves, how the security structure on the Korean Peninsula will change, and what alternatives are being discussed regarding the future governance of the Korean Peninsula and reunification.